TRANSFORMASI KARAKTER SISWA MELALUI PELATIHAN HADRAH: ANALISIS DI MI TARBIYATUL WATHAN KRAKSAAN - M Mahbubi; Lailul Vicky Zawawi Imron; Abdul Hayyi (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
Character education plays a crucial role in shaping students who are not only intellectually capable but also disciplined, responsible, and morally upright. In this context, hadrah training, as a traditional Islamic art form, is believed to have strong potential as a medium for character development in Islamic elementary schools. This study aims to analyze the transformation of student character through hadrah training at MI Tarbiyatul Wathan Kraksaan, Probolinggo. Employing a qualitative approach with a case study design, the research involved observations of hadrah training activities, interviews with teachers and students, and documentation of the program. The collected data were analyzed using Miles and Huberman’s interactive model through data reduction, data display, and conclusion drawing. The results reveal that hadrah training significantly contributes to the formation of student character, especially in aspects of discipline, cooperation, responsibility, and religiosity. Students also developed stronger social bonds and a deeper appreciation of Islamic traditions. The novelty of this study lies in its focus on hadrah not merely as a cultural performance or religious practice, but as a pedagogical strategy for character transformation in madrasah ibtidaiyah, an area rarely explored in previous research. These findings provide practical implications for strengthening character education curricula through Islamic cultural arts in schools.